FAKTOR PENENTU PROFITABILITAS BPR SYARIAH DAN EFEK PERATURAN DAERAH: STUDI KASUS PROVINSI ACEH - Azis, Saiful; Al Muizzuddin Fazaalloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This Nanggroe Aceh Darussalam is a province with the highest percentage of Muslim population in Indonesia. This is accompanied by the special privilege given to Aceh to implement local regulations in the form of Qanun LKS, which regulates financial institutions based on Islamic Sharia principles. The purpose of this study is to analyze the factors that determine the profitability level of Sharia-based Rural Banks (BPR Syariah) in Aceh province, as well as the effect of Qanun LKS regulations. The data used in this study is panel data with a period from 2012 to 2021. The estimation method used is pooled OLS with a random effects model. The results of this study indicate that the Capital Adequacy Ratio (CAR) and Financing to Deposite Ratio (FDR) have a positive influence on profitability, as represented by Return on Assets (ROA), of Sharia-based Rural Banks in Aceh province. On the other hand, Operating Expenses and Operating Income (BOPO) have a negative impact on profitability. However, the Non Performing Finance (NPF) variable and the Qanun LKS dummy variable are not significant in influencing the profitability of Sharia-based Rural Banks in Aceh province.